Environmental Risk Management and Audit Costs: A Review of Literature on the Role of Stringent Environmental Policies - Muhammad Rizal; Yessica Amelia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This qualitative literature review explores the impact of stringent environmental policies on environmental risk management and audit costs. It investigates the evolving role of environmental regulations in shaping corporate risk management strategies, particularly focusing on how businesses address environmental risks and the associated costs of audits. The review synthesizes findings from various studies, highlighting the importance of integrating environmental risk management into corporate governance structures to mitigate financial and legal risks. It also emphasizes the necessity of environmental audits in ensuring compliance with regulatory frameworks, despite their associated costs. The review concludes that while the initial costs of environmental audits may be high, their long-term benefits, including regulatory compliance, risk reduction, and improved stakeholder relations, justify the investment. Future research should address the challenges faced by SMEs and explore the geographical and sector-specific differences in managing environmental risks.